Economic and legal aspects of using rail transport for the carriage of dangerous goods - Piękoś, Dominik; Piękoś, Aleksandra (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
The aim of the article is to analyse the use of rail transport for the carriage of dangerous goods, with particular emphasis on the specifics of military transport. The study presents fundamental concepts related to transport, the transport system, and the characteristics of dangerous goods. Current legal regulations and cost calculation procedures for transport are discussed. Based on a case study of an actual transport of unleaded 95 petrol, a practical logistical analysis and cost calculation were provided.